3(x - 4) = 5(x + 2)

(1 point)
Responses
• x = 11
• x = -11
• x = 1
• x = -1

1 answer

To solve the equation 3(x - 4) = 5(x + 2), you can start by distributing the numbers to eliminate the parentheses:

3x - 12 = 5x + 10

Next, you can simplify the equation by combining like terms:

-12 - 10 = 5x - 3x

-22 = 2x

Finally, you can solve for x by dividing both sides of the equation by 2:

-22/2 = x

x = -11

Therefore, the correct answer is x = -11.
Similar Questions
  1. The eye is an organ of which major body system? (1 point)Responses skeletal integumentary muscular nervous Which statement best
    1. answers icon 7 answers
    1. answers icon 1 answer
  2. The number line shows the locations of points P, Q, R, and S.Which points have a distance of 5 units between them? (2 points)
    1. answers icon 1 answer
  3. Which point on the number line best represents 5–√ ?________A__B_C____D______ 0 1 2 3 4 5 6 7 (1 point) Responses Point A
    1. answers icon 1 answer
more similar questions